Hepatocellular carcinoma with uncommon sites of metastasis: a rare case report - Mangala Targe (The Egyptian Journal of Radiology and Nuclear Medicine, 2021)
Abstract Background Hepatocellular carcinoma (HCC) is a highly malignant tumor, causing both intrahepatic and extrahepatic metastases. The extrahepatic metastasis occurs in one-third of patients with HCC and it is associated with a poor prognosis. The most common sites of extrahepatic metastasis are lung, regional lymph nodes, bone, adrenal glands, and peritoneum/omentum. Detection of such extrahepatic metastasis plays a vital role in the staging and treatment planning of HCC. Case presentation A 60-year-old man was presented to our centre with loss of apetite, generalised weakness, and weight loss. Abdominal examination revealed a firm lump in the right hypochondrium. CT findings revealed a large well-defined hypodense mass in almost entire right lobe of the liver. A well-defined oval, heterogeneously enhancing soft tissue mass lesions were also noted in both adrenal glands and psoas muscles. For histopathological diagnosis, percutaneous ultrasound-guided truecut biopsy was done from right lobe liver mass confirming well differentiated HCC. Conclusions In the present case report, we present an extremely rare and unique case of HCC with disseminated skeletal muscle metastasis with concomitant bilateral axillary lymph node metastasis. It is crucial for radiologists to detect such extrahepatic sites of metastasis initially at the time of diagnosis for accurate staging and treatment planning for a better prognosis.